Tetracycline-resistance encoding plasmids from Paenibacillus larvae, the causal agent of American foulbrood disease, isolated from commercial honeys - Alippi, Adriana Mónica (2014)
Paenibacillus larvae, the causal agent of American foulbrood disease in honeybees, acquires tetracycline-resistance via native plasmids carrying known tetracycline-resistance determinants. From three P. larvae tetracycline-resistant strains isolated from honeys, 5-kb-circular plasmids with almost identical sequences, designated pPL373 in strain PL373, pPL374 in strain PL374, and pPL395 in strain PL395, were isolated. These plasmids were highly similar (99%) to small tetracycline- encoding plasmids (pMA67, pBHS24, pBSDMV46A, pDMV2, pSU1, pAST4, and pLS55) that replicate by the rolling circle mechanism. Nucleotide sequences comparisons showed that pPL373, pPL374, and pPL395 mainly differed from the previously reported P. larvae plasmid pMA67 in the oriT region and mob genes. These differences suggest alternative mobilization and/or conjugation capacities. Plasmids pPL373, pPL374, and pPL395 were individually transferred by electroporation and stably maintained in tetracycline-susceptible P. larvae NRRL B-14154, in which they autonomously replicated. The presence of nearly identical plasmids in five different genera of gram-positive bacteria, i.e., Bhargavaea, Bacillus, Lactobacillus, Paenibacillus, and Sporosarcina, inhabiting diverse ecological niches provides further evidence of the genetic transfer of tetracycline resistance among environmental bacteria from soils, food, and marine habitats and from pathogenic bacteria such as P. larvae.